The Impact of Integrating Outdoor Education-Based Learning in the Elementary Education Curriculum on Students' Emotional Intelligence - Ahmad, Endang Putri; Chalid, Hasan (Trigin Institute, 2025)
This research examines the impact of integrating outdoor education-based learning into the elementary education curriculum on students' emotional intelligence (EI). Emotional intelligence, which includes key competencies such as self-awareness, empathy, emotional regulation, and social skills, plays a critical role in students' academic success and overall well-being. Outdoor education provides an experiential learning environment that promotes these emotional competencies through hands-on, nature-based activities. By engaging with their environment and peers in non-traditional settings, students have opportunities to develop critical social-emotional skills that are essential for personal and academic growth. Through a mixed-methods approach, this study explores the experiences of elementary students participating in outdoor learning activities, focusing on how these activities impact their emotional intelligence. Findings indicate a positive relationship between outdoor education and the development of emotional intelligence, highlighting improvements in areas such as emotional regulation, empathy, and interpersonal relationships. However, challenges related to logistics, teacher preparedness, and the inclusivity of outdoor activities are identified as potential barriers to fully realizing the benefits of outdoor education. This research contributes to the growing body of literature supporting the integration of outdoor learning in school curricula as a strategy for enhancing emotional intelligence and social-emotional development. The study's findings emphasize the need for further investigation into long-term impacts, as well as the development of teacher training programs to facilitate effective outdoor learning experiences. Future research should also focus on exploring how diverse student populations respond to outdoor education and how different types of outdoor activities can foster specific emotional intelligence competencies.